Operando study of palladium nanoparticles inside UiO-67 MOF for catalytic hydrogenation of hydrocarbons. (25th May 2018) - Bugaev, A. L.; Guda, Alexander A.; Lomachenko, Kirill A.; Kamyshova, Elizaveta G.; Soldatov, Mikhail A.; Kaur, Gurpreet; Øien-Ødegaard, Sigurd; Braglia, Luca; Lazzarini, Andrea; Manzoli, Maela; Bordiga, Silvia; Olsbye, Unni; et al.
Abstract : Formation of Pd nanoparticles inside UiO-67 MOF was monitored by in situ X-ray absorption and diffraction. Abstract : Functionalization of metal–organic frameworks with metal nanoparticles (NPs) is a promising way for producing advanced materials for catalytic applications. We present the synthesis and in situ characterization of palladium NPs encapsulated inside a functionalized UiO-67 metal–organic framework. The initial structure was synthesized with 10% of PdCl2 bpydc moieties with grafted Pd ions replacing standard 4, 4′-biphenyldicarboxylate linkers. This material exhibits the same high crystallinity and thermal stability of standard UiO-67. Formation of palladium NPs was initiated by sample activation in hydrogen and monitored by in situ X-ray powder diffraction and X-ray absorption spectroscopy (XAS). The reduction of Pd II ions to Pd 0 occurs above 200 °C in 6% H2 /He flow. The formed palladium NPs have an average size of 2.1 nm as limited by the cavities of UiO-67 structure. The resulting material showed high activity towards ethylene hydrogenation. Under reaction conditions, palladium was found to form a carbide structure indicated by operando XAS, while formation of ethane was monitored by mass spectroscopy and infra-red spectroscopy.